PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BUANA CENTRA SWAKARSA CILEGON BANTEN - Ipan Hilmawan (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This research was conducted to examine the Effect of Work Discipline, Work Motivation, and Job Satisfaction on Employee Performance at PT. Buana Centra Swakarsa Cilegon-Banten. From the problem of this research, the previous research was conducted, then three hypotheses were formulated, namely H1, H2, H3. The method in this study is descriptive that uses a sample of 82 respondents with questionnaire research instruments compiled based on indicators of Work Discipline (X1), Work Motivation (X2), Job Satisfaction (X3), and Employee Performance (Y). The results of data processing show that partially Work Discipline has a significant positive effect on employee performance at PT Buana Centra Swakarsa, Work motivation has a significant positive effect on employee performance at PT Buana Centra Swakarsa, Job Satisfaction significant negatively affects employee performance at PT Buana Centra Swakarsa.